2001
DOI: 10.1302/0301-620x.83b1.10062
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bone remodelling around hydroxyapatite-coated, porous-coated and grit-blasted hip replacements retrieved at post-mortem

Abstract: We investigated the implant-bone interface around one design of femoral stem, proximally coated with either a plasma-sprayed porous coating (plain porous) or a hydroxyapatite porous coating (porous HA), or which had been grit-blasted (Interlok). Of 165 patients implanted with a Bimetric hip hemiarthroplasty (Biomet, Bridgend, UK) specimens were retrieved from 58 at post-mortem. We estimated ingrowth and attachment of bone to the surface of the implant in 21 of these, eight plain porous, seven porous HA and six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(32 citation statements)
references
References 18 publications
0
30
1
1
Order By: Relevance
“…However, bone ongrowth in the porous HA-coated regions was distributed more evenly without large differences. As they also noted more ingrowth and ongrowth of bone to the porous HA-coated surface, it is thought the HA counteracts the bone resorptive action of the local stress shielding, at least during the early postoperative years [5].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, bone ongrowth in the porous HA-coated regions was distributed more evenly without large differences. As they also noted more ingrowth and ongrowth of bone to the porous HA-coated surface, it is thought the HA counteracts the bone resorptive action of the local stress shielding, at least during the early postoperative years [5].…”
Section: Discussionmentioning
confidence: 98%
“…However, these opposing processes of bone gain and loss do not work at the same time, but whether they persist and to what degree are unknown. Although short-term retrieval studies report the HA coating after 2 to 4 years implantation is partly broken down through osteoclastic resorption [2,3,5,10,11,18,19,27,28], none of these studies reported whether patient demographics might influence residual HA coating or bone ongrowth. Therefore, we asked three questions: (1) Is the resorption of HA coating and bone ongrowth mainly correlated with time in vivo or with demographics, and when time in vivo is predominant, at which point can we expect all the HA to have completely resorbed?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,12 Osteointegration may be confirmed by the presence of bridging bone formation between the endosteum and the prosthesis. 4,7,9,13 Long-term remodelling of this peri-prosthetic bone is vital for component survival. 4,13 The surface finish of the implant plays a vital role in the host bone/component reaction, and different surface finishes have been employed with varying success.…”
Section: Discussionmentioning
confidence: 99%